The Implementation of Innovation Program Report: 3 in 1 Anion Bed Operating Pattern For Water Efficiency and Water Pollution Loads Improvement - SUSILO, Sofiyan Dwi; PRASETYO, Arif Eko; SETYAWAN, Wawan; ICHWAN, Munirul; INTAN, Indo; KARNYOTO, Andrea Stevens (PT Keberlanjutan Strategis Indonesia, 2024)
In Tuban Regency, East Java, Indonesia, PT PLN Nusantara Power Unit Tanjung Awar-Awar Power Plant was built. There are two 350 MW coal-fired plants in operation. This project was built based on Presidential Regulation of the Republic of Indonesia No 71 of 2006 dated July 5, 2006 concerning assignment to PT PLN. The company is committed to the environment. They hire a highly skilled team of technicians and engineers to run water treatment plants (WTP). The PT PLN Nusantara Power Unit Tanjung Awar-Awar was able to solve many problems that were caused by the WTP by analyzing data and observing actual conditions. Specially to address concerns such as efficiency, safety, and saving money. A challenge of WTP operation is the limited ability of ion exchange resin (Anion) to remove impure ions from raw water. Hence, PLN introduced an innovative program called